2005
DOI: 10.1007/s10534-004-4491-7
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial content of selected elements in experimental anthracycline-induced cardiomyopathy in rabbits

Abstract: Cardiotoxicity represents the main drawback of clinical usefulness of anthracycline antineoplastic drugs. In this study, a content of selected elements (Ca, Mg, K, Se, Fe) in the post-mortem removed samples of the myocardial tissue was studied in three groups of rabbits: 1) control group (i.v. saline; n = 10); 2) daunorubicin-receiving animals (DAU; 3 mg/kg, i.v; n = 11); 3) animals receiving cardioprotective iron-chelating agent dexrazoxane (DEX; 60 mg/kg, i.p.; n = 5) prior to DAU. Drugs were administered on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 30 publications
2
11
2
Order By: Relevance
“…In addition, anthracyclines and their metabolites have been reported to induce a number of distinct cellular effects, which do not appear to be ROS-mediated (Menna et al, 2007). For example, anthracyclines have been demonstrated to induce a number of perturbations in cellular calcium homeostasis (Simunek et al, 2005b;Wallace, 2007). Unlike in the case of selective iron chelator L1, it can not be excluded that dexrazoxane may also chelate calcium, which can potentially account for the difference in cardioprotective effects of both chelators.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, anthracyclines and their metabolites have been reported to induce a number of distinct cellular effects, which do not appear to be ROS-mediated (Menna et al, 2007). For example, anthracyclines have been demonstrated to induce a number of perturbations in cellular calcium homeostasis (Simunek et al, 2005b;Wallace, 2007). Unlike in the case of selective iron chelator L1, it can not be excluded that dexrazoxane may also chelate calcium, which can potentially account for the difference in cardioprotective effects of both chelators.…”
Section: Discussionmentioning
confidence: 99%
“…Others have documented that DEX (40 mg/ kg) markedly reduces deleterious effects of DOX (2 mg/kg, weekly for 4 weeks) on trabecular actin-myosin crossbridge cycle (45). DEX (60 mg/kg weekly) was also able to prevent an increase in myocardial total calcium content induced by chronic DAU treatment (3 mg/kg, weekly for 10 weeks) (241). Interestingly, in the latter study, the chronic ANT treatment with or without DEX had no impact on total myocardial iron levels.…”
Section: Cardioprotection Against Ant Cardiotoxicity In Vivomentioning
confidence: 98%
“…It seems to be contradictory, based on the fact that lower levels of Mg were associated to cardio toxicity. Nevertheless previous studies about the doxorubicin cardiotoxic effects also reported an increase of Mg levels after chemotherapy administration [41] [42]. Doxorubicin a widely chemo-therapeutic agent, used for BC, and other types of cancer treatment.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that DOX induces an iron mediated increase in ROS, referred to as the "ROS and iron hypothesis". According to this hypothesis, in the presence of iron, DOX leads to futile redox cycling, inducing substantial ROS production and cellular damage [51] [52] [42]. Ichikawa et al (2014) [53] show that the cardiotoxicity of DOX occurs through preferential accumulation of iron specifically in the mitochondria and that a reversal in mitochondrial iron accumulation alleviates the deleterious effects of DOX on the heart.…”
Section: Discussionmentioning
confidence: 99%